‘Reality is for Those who Cannot Sustain the Dream’: Fantasies of Selfhood in Legal Texts - Mańko, Rafał (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
Confronting the law as a form of ideology is not an easy task, especially for lawyers very strongly attached to the internal point of view as part of their professional habitus. Despite this difficulty, the present paper aims at contributing to the ideological demistification of law by proposing to apply Slavoj Žižek’s critique of ideology to the legal field. In particular, the paper elaborates a specific methodology of subjecting legal texts to a critique of ideology by way of identifying the symptoms, i.e. points of breakdown of the ideological field which are simultaneously necessary for that field to achieve its closure. The paradox of symptoms is that they are inevitable for the ideological field, yet at the same time they undermine it, opening up a space for its critique. In this context, the aim of this paper is to confront the fundamental fantasies conveyed by legal ideology. The paper approaches ideological fantasies in strict connection with ideological interpellation, i.e. the process in which a human individual is transformed into a subject of ideology. Ideological interpellation of individuals into subjects is one of the chief operations of the law, which, in its current form, is based on the fundamental assumption that human beings are subjects of rights and duties. Directing the critique of ideology at legal texts aims at undermining the efficacy of the ideological grip held by the Symbolic order upon individuals by insisting on the classical Lacanian thesis that ‘the big Other does not exist’. On a practical level, critique of legal ideology performed by lawyers themselves can help to bring about a more reflexive approach to their participation in the principal practices of legal culture and can help to raise lawyers’ awareness regarding their role in society.
Keywords: ideologiczna demistyfikacji prawa; Žižek, Slavoj